Scarf Adhesive Joints between Different Adherends by Experimental and Numerical Modelling - D. L. Alves; R. D. S. G. Campilho; R. D. F. Moreira (Technological Innovation in Engineering Research Vol. 7, 2022)
Nowadays, in many high-performance structures, it is necessary to combine composite materials with other light-weighted metals such as aluminium or titanium, for the purpose of structural optimization. More common joint configurations are double-lap, stepped and scarf joints. This paper presents the results of an experimental and numerical investigation for hybrid scarf joints between adherends made of aluminium and composite materials, taking into account various scarf angle (\(α\)) values. The numerical analysis by Finite Elements (FE) enabled the obtainment of peel (\(σ\)y) and shear stresses (\(τ\)xy), which are then used to discuss the strength between different joint configurations. Cohesive zone modelling (CZM) was utilised to forecast the joint strength, and the predictions were then validated by comparing the results to those from the experiments. CZM were verified for the design of hybrid scarf joints because the joints’ behaviour was significantly dependent on \(α\) , and CZM were validated for the design process of hybrid scarf joints.